Pengaruh Stres Kerja, Beban Kerja, dan Kompensasi Terhadap Kinerja Guru dan Karyawan SMK Diponegoro Banyu Putih - Vita, Inka Nuromavita (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2024)
The purpose of this study was to analyze work stress, workload, and compensation on the performance of teachers and employees SMK Diponegoro Banyu putih. This sampling method uses a random sample technique and the number of samples in this study is 100 teachers an employees. The data used is primary data. Data obtained directly ftom SMK Diponegoro Banyu putih through the quesionnaire method. The primary data was then processed an analized using SPSS The collected data was then analyzed using multiple linier regression. The result of this study indicate that work stress has a positive and significant effect on performance, workload has a positive and significant effect on performance, Compensation has a positive and significant effect on performance